Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbentuk Booklet Pada Pembelajaran IPAS di Kelas IV Sekolah Dasar - Defriwanti, Wita; Erita, Yeni; Engreini, Syofianti; Hamimah, Hamimah (Universitas Pendidikan Indonesia (UPI), 2025)
This study aims to develop booklet-style Student Worksheets (LKPD) that are valid, practical, and effective for teaching science to fourth-grade elementary students. It addresses the lack of engaging LKPDs that encourage active student participation in learner-centered environments. Using the Research and Development (RD) method with the ADDIE model, the study was conducted in three elementary schools. Data were collected through observation, interviews, expert validation, questionnaires for teachers and students, and pretest-posttest assessments. The LKPD showed a validity score of 96.53%, practicality scores of 97.5% from teachers and 93.3% from students, and effectiveness with N-Gain values between 79.35% and 83.25%. This LKPD assists teachers in organizing materials and evaluations while promoting students’ active learning, critical thinking, and scientific skills. Therefore, the booklet LKPD is suitable and effective for elementary science education.